Successful functional aging in middle-aged and older adults with HIV - Fazeli, Pariya L. (AIDS Behav, 2020)
People living with HIV (PLWH) experience greater everyday functioning impairment. We examined frequency and correlates of successful functional aging (SFA) in PLWH. Using gold-standard questionnaires, SFA was defined in 174 HIV+ and 71 HIV- adults as absence of significant everyday cognitive symptoms and declines in instrumental activities of daily living. More HIV- (45%) than HIV+ (18%) adults met SFA criteria (p<0.01). Depression, cognitive functioning, socioeconomic status, and HIV status were independent correlates of SFA (p-values<0.05). Motor ability, learning, and verbal fluency were associated with SFA. SFA was associated with health-related quality of life (HRQoL). PLWH are three times less likely to achieve SFA than HIV- adults, a phenotype that translates to HRQoL. While SFA is multifactorial, driven by clinico-demographic factors, HIV may pose additional risk to achieving SFA. Further work should examine other mechanisms whereby HIV hinders SFA (e.g., biomarkers, stress, mental health) and ultimately inform interventions to facilitate SFA.